Donor Age, Donor-Recipient Size Mismatch, and Kidney Graft Survival - Lepeytre, Fanny (Clin J Am Soc Nephrol, 2020)
BACKGROUND AND OBJECTIVES: Small donor and/or kidney sizes relative to recipient size are associated with a higher risk of kidney allograft failure. Donor and recipient ages are associated with graft survival and may modulate the relationship between size mismatch and the latter. The aim of this study was to determine whether the association between donor-recipient size mismatch and graft survival differs by donor and recipient age. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENT: We performed a retrospective cohort study of first adult deceased donor kidney transplantations performed between 2000 and 2018 recorded in the Scientific Registry of Transplant Recipients. We used multivariable Cox proportional hazards models to assess the association between donor-recipient body surface area ratio and death-censored graft survival, defined as return to dialysis or retransplantation. We considered interactions between donor-recipient body surface area ratio and each of recipient and donor age. RESULTS: Among the 136,321 kidney transplant recipients included in this study, 23,614 (17%) experienced death-censored graft loss over a median follow-up of 4.3 years (interquartile range, 1.9–7.8 years). The three-way donor-recipient body surface area ratio by donor age by recipient age interaction was statistically significant (P=0.04). The magnitude of the association between severe size mismatch (donor-recipient body surface area ratio <0.80 versus ≥1.00) and death-censored graft survival was stronger with older donor age and recipient age. In all recipient age categories except the youngest (18–30 years), 5- and 10-year graft survival rates were similar or better with a size-mismatched donor aged <40 years than a nonsize-mismatched donor aged 40 years or older. CONCLUSIONS: The association of donor-recipient size mismatch on long-term graft survival is modulated by recipient and donor age. Size-mismatched kidneys yield excellent graft survival when the donor is young. Donor age was more strongly associated with graft survival than size mismatch.